Systematic review of interventions to increase the delivery of preventive care by primary care nurses and allied health clinicians. (December 2015) - McElwaine, Kathleen; Freund, Megan; Campbell, Elizabeth; Bartlem, Kate; Wye, Paula; Wiggers, John
Abstract Background Primary care nurses and allied health clinicians are potential providers of opportunistic preventive care. This systematic review aimed to summarise evidence for the effectiveness of practice change interventions in increasing nurse or allied health professional provision of any of five preventive care elements (ask, assess, advise, assist, and/or arrange) for any of four behavioural risks (smoking, inadequate nutrition, alcohol overconsumption, physical inactivity) within a primary care setting. Methods A search of Medline, Embase, PsycInfo, and CINAHL databases was undertaken to locate controlled intervention trials published between 1992 and May 2014 that provided practice change interventions to primary care nurses and/or allied health professionals to increase preventive care. The effect of interventions aimed at increasing the provision of any of the five care elements for any of the four behavioural risks was examined. A narrative synthesis was utilised. Results From 8109 articles, seven trials met the inclusion criteria. All trials bar one, assessed multi-strategic practice change interventions (three to five strategies) focused on care by nurses (six trials) or mixed nursing/allied health clinicians. One trial examined care provision for all four risks, five trials examined care for smoking only, and one trial examined care for alcohol consumption only. For the six trials reporting significance testing (excludes one smoking care trial), significant effects favouring the intervention group were reported in at least one trial for smoking risk assessment (2/4 trials reported an effect for at least one analysis of an assessment outcome), brief advice (2/3), assistance (2/2), and arranging referral (2/3); alcohol risk assessment (1/2) and brief advice (1/2); inadequate nutrition risk assessment (1/1); and physical inactivity risk assessment and brief advice (1/1). When the number of analyses undertaken within trials focusing on smoking care was considered, the results were less promising (e.g. of the 15 analyses conducted on brief advice variables across three trials, four showed a positive effect). Conclusions Evidence for the effect of practice change interventions on preventive care by primary care nurses or allied health providers is inconclusive given the small number of trials and inconsistency of results between and within trials. Systematic review registration number None